Ultrafast transient absorption spectroelectrochemistry: femtosecond to nanosecond excited-state relaxation dynamics of the individual components of an anthraquinone redox couple. Issue 2 (17th December 2021) - Goia, Sofia; Turner, Matthew A. P.; Woolley, Jack M.; Horbury, Michael D.; Borrill, Alexandra J.; Tully, Joshua J.; Cobb, Samuel J.; Staniforth, Michael; Hine, Nicholas D. M.; Burriss, Adam; Macpherson, Julie V.; Robinson, Ben R.; et al.
Abstract : A spectroelectrochemical set-up using a boron doped diamond mesh electrode is presented; from ultrafast photodynamics to steady-state, the photochemistry and photophysics of redox active species and their reactive intermediates can be investigated. Abstract : Many photoactivated processes involve a change in oxidation state during the reaction pathway and formation of highly reactive photoactivated species. Isolating these reactive species and studying their early-stage femtosecond to nanosecond (fs–ns) photodynamics can be challenging. Here we introduce a combined ultrafast transient absorption-spectroelectrochemistry (TA-SEC) approach using freestanding boron doped diamond (BDD) mesh electrodes, which also extends the time domain of conventional spectrochemical measurements. The BDD electrodes offer a wide solvent window, low background currents, and a tuneable mesh size which minimises light scattering from the electrode itself. Importantly, reactive intermediates are generated electrochemically, via oxidation/reduction of the starting stable species, enabling their dynamic interrogation using ultrafast TA-SEC, through which the early stages of the photoinduced relaxation mechanisms are elucidated. As a model system, we investigate the ultrafast spectroscopy of both anthraquinone-2-sulfonate (AQS) and its less stable counterpart, anthrahydroquinone-2-sulfonate (AH2 QS). This is achieved by generating AH2 QS in situ from AQS via electrochemical means, whilst simultaneously probing the associated early-stage photoinduced dynamical processes. Using this approach we unravel the relaxation mechanisms occurring in the first 2.5 ns, following absorption of ultraviolet radiation; for AQS as an extension to previous studies, and for the first time for AH2 QS. AQS relaxation occurs via formation of triplet states, with some of these states interacting with the buffered solution to form a transient species within approximately 600 ps. In contrast, all AH2 QS undergoes excited-state single proton transfer with the buffered solution, resulting in formation of ground state AHQS − within approximately 150 ps.